MENEROPONG KEYAKINAN ATONI PAH METO ATAS EKSISTENSI TUHAN: SUATU PERSPEKTIF FILOSOFIS KETUHANAN - Rolin Ferdilianto Sandelgus Taneo (STP St. Bonaventura Medan, 2025)
This paper aims to describe the belief system of the Timor Island community (Atoni Pah Meto). In general, it can be summarized that the Atoni Pah Meto believe in Uis Neno (God of Heaven) and Uis Pah (God/Mother Earth). This belief system makes the Atoni Pah Meto aware of the existence of transcendent power, but at the same time, this belief also believes that this transcendent power bestows His blessings through the earth. Therefore, the earth is seen as the Mother who gives life. The implications of this belief can also be seen in how the Atoni Pah Meto preserve nature. Using the theoretical foundation of perennialism philosophy, the author will further examine this topic and also see what positive values ​​exist within the Atoni Pah Meto belief system for the sustainability of religious life and daily practice.